2022
DOI: 10.1002/suco.202200106
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the effect of hybrid fiber reinforced on the flexural behavior of RC beams having different lap‐spliced lengths

Abstract: There are only a few studies related to the effect of the hybrid fiber reinforcement on the flexural behavior of full‐scale beam specimens having lap‐spliced length. Thus, this study will ensure important experimental data about the effect of macro steel fibers blended with micro steel fibers on lap‐spliced length. The aim of this study was to investigate the influence of hybrid steel fiber reinforcement on the flexural behavior of full‐scale reinforced concrete beams having different lap‐spliced bars. A sum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In most of the studies, the deflection-based ductility index 23,26,27 or displacement ductility ratio 11,20,21 have been used as an indicator of ductility, but the behavior of the lap splice in the plastic region has not been studied in depth. Micallef and Vollum 28 and Gillani et al, 26 studied the local behavior of lapped bars after yielding by using the strain gauges in lapped bars.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the studies, the deflection-based ductility index 23,26,27 or displacement ductility ratio 11,20,21 have been used as an indicator of ductility, but the behavior of the lap splice in the plastic region has not been studied in depth. Micallef and Vollum 28 and Gillani et al, 26 studied the local behavior of lapped bars after yielding by using the strain gauges in lapped bars.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have done a lot of research on the effect of different types of fibers on the different properties of concrete, including its mechanical properties, and all the evidence indicates that the use of fibers alone or in a hybrid form can improve the mechanical behavior of fibers. Also, the use of environmentally friendly additives along with fibers, besides being sustainable, can help make high‐performance concrete 40–49 …”
Section: Introductionmentioning
confidence: 99%
“…Also, the use of environmentally friendly additives along with fibers, besides being sustainable, can help make high-performance concrete. [40][41][42][43][44][45][46][47][48][49] Previous research has shown that the use of recycled polypropylene fiber improves the mechanical behavior and durability of concrete. 50,51 In this paper, the macro-synthetic fibers, Forta and Barchip, were made of polyolefin.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the brittleness and flexural strength and toughness of concrete by adding fibers is one of the most common methods for toughening concrete at this stage, [15][16][17][18][19] which is known as fiber-reinforced concrete (FRC). The addition of fiber can force the extension path of the crack tip in the concrete to change or make expected large cracks become an increasingly subtle crack field, increasing the energy consumed for crack development and playing a role in crack resistance and toughening.…”
Section: Introductionmentioning
confidence: 99%